Charlie Bumpers vs. The Squeaking Skull - Harley, Bill, 1954-; Gustavson, Adam (Atlanta, Georgia : Peachtree Publishers, 2014)
As Halloween nears, Charlie and Tommy hope to get out of taking their little sisters trick-or-treating and go by themselves to Alex's upscale neighborhood instead, then attend a sleepover at Alex's house, but when Charlie learns that partygoers will be watching a very scary horror movie he panics.
Keywords: Halloween -- Juvenile fiction; Fear -- Juvenile fiction; Schools -- Juvenile fiction; Families -- Juvenile fiction; Humorous stories; Halloween -- Fiction; Fear -- Fiction; Schools -- Fiction; Family life -- Fiction; Humorous stories